2020
DOI: 10.14202/vetworld.2020.542-548
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of foot-and-mouth disease viruses collected from Northern and Central Ethiopia during the 2018 outbreak

Abstract: Background and Aim: Foot-and-mouth disease (FMD) is endemic in several developing countries and affects poor farmers through loss of production, death of diseased animals, and loss of animal byproducts. Forty-three samples were collected from 12 sites of five geographical located areas from suspected FMD virus (FMDV)-infected cattle during 2018. This study aimed to isolate and characterize the FMDVs using reverse transcription-polymerase chain reaction (RT-PCR) and gene sequencing. Materials and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
3
8
0
Order By: Relevance
“…The obtained results were observed as reported previously (El-Sayed et al 2013;Huang et al 2011). The results of viral isolation indicated that Eleven samples out of a total of 209 samples showed specific CPE characterized by granulation, cell rounding, and rapid destruction of BHK-21 monolayer cell within 48h-72 has described by Yeneneh et al (2020) and Ding et al (2013). These results in agreement with (Attia et al .2016) who reported that virus isolation on BHK-21 is the most reliable diagnostic method.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The obtained results were observed as reported previously (El-Sayed et al 2013;Huang et al 2011). The results of viral isolation indicated that Eleven samples out of a total of 209 samples showed specific CPE characterized by granulation, cell rounding, and rapid destruction of BHK-21 monolayer cell within 48h-72 has described by Yeneneh et al (2020) and Ding et al (2013). These results in agreement with (Attia et al .2016) who reported that virus isolation on BHK-21 is the most reliable diagnostic method.…”
Section: Discussionsupporting
confidence: 86%
“…These findings were in close agreement with the findings of Amr Hassan 2016) who described the infectivity and antigenicity of the virus yield were examined at 24hr. The low level of viral isolation may be attributed to pH levels and climatic changes which lead to decrease infectivity of the isolated virus, as the level of isolation on BHK21 may have depended on a live virus, as reported earlier (Shaw et al 2004;Yeneneh et al 2020).…”
Section: Discussionmentioning
confidence: 76%
“…It has long been appreciated that individual buffalo may harbour two, or even three different SAT serotypes at one time, and may remain persistently infected for extended periods of up to several years [7,8]. Many examples of mixed serotype infections in cattle have also been documented [9][10][11][12], and more than one strain of the same serotype has been identified within a single sample [12]. Coinfection with antigenically diverse strains is of particular concern due to the increased risk associated with the generation of novel recombinant viruses with the potential to evade immune responses raised against previously circulating strains.…”
Section: Introductionmentioning
confidence: 99%
“…Several outbreak studies showed that four of the seven serotypes (O, A, SAT-1, and SAT-2) were reported in the country in the order of the dominancy of their occurrence and the economic loss they incur [19,20]. The continuous occurrence of serotype O, A, and SAT-2 was confirmed by recent retrospective studies of Gizaw et al [21] and Tesfaye et al [22]. Serotype O and A were reported in all parts of Ethiopia as well as SAT-1 and SAT-2 in the central and southern half of the country, where 70% of the country's cattle population is found.…”
Section: Introductionmentioning
confidence: 84%
“…The chance of being sero-positive was higher in adult animals (>18 months) with OR: 6, 95 % CI, [2,18] as compared to their younger counterparts. Caprine species were seen to have 3.8% sero-positivity, but the chance was eight times higher (OR: 8, 95% CI, [3,22]) for ovine as compared to caprine. Although statistical inference with this small sample size for ovine samples is difficult.…”
Section: Sero-prevalence Of Fmd In Domestic Small Ruminantsmentioning
confidence: 92%